Processos educativos e de aprendizagem na biblioteca universitária: abordagem centrada no estudo de usuários - Oliveira, Flávia Reis de (My University, 2020)
This thesis aims is to weave directives to reconfigurate the university library in contemporary times with the purpose to the qualification of educational and learning processes mediated by library and, according to this point, appears the following question: what indicators allow to qualify the services that the university library offers in order to place them in favor of the learning of its users? The theoretical basis is anchored in Paulo Freire and John Dewey, with discussions about autonomy; respect for knowledge; commitment to quality and equal education; theory combined with practice; learning that transforms the subject and knowledge; the relationship with the other; and learning through experience by means dialogue, in which the human being and the environment are modified in and by the interaction that can enhance the educational and learning processes. The methodological path was the qualitative research, so that the data were constructed via a case study at the Hugo Dantas da Silveira Central Library, at the Federal University of Rio Grande / RS, through document analysis of library management reports, interviews were made with librarians working in the technical unit and focus group with some users. The sample comprised 12 librarians and 7 users. The data were treated by means of textual discursive analysis, by Moraes and Galiazzi (2003; 2011), and, at the intersection of the analyzes between the instruments used, it was identified that the points highlighted in the narratives point out singularities for the configuration of the university library. The final considerations, is about configurate new systems and organizations, both in the order and structure of physical spaces, as well as in the organization of the collections, services and products offered. From the narratives, it was identified that users and librarians attribute to the library a fundamental role in the qualification of academic learning, and legitimize it as a space that can be constituted by the democratization of access for information, by the mediation between information and registered knowledge and , mainly, for the constitution of spaces that contribute to learning. The guidelines for reconfiguring the Library, based on the data constructed and analyzed in this investigation, legitimize it as an environment of encouragement and constitution for learning, since, in addition to disseminating and managing the knowledge produced and stored in its various supports and devices, it works to promote actions to search, interact and disseminate information. This research reiterates that the library in the context of learning is mobilizing, performing an educational function and mediating for the democratization of access to information and develop the knowledge.
Esta tese tem como objetivo tecer diretrizes para reconfiguração da biblioteca universitária na contemporaneidade com vistas à qualificação dos processos educativos e de aprendizagem mediados por ela e, assim, questiona: que indicadores permitem qualificar os serviços que a biblioteca universitária oferece no sentido de colocá-los a favor da aprendizagem dos seus usuários? O embasamento teórico está ancorado em Paulo Freire e John Dewey, com discussões acerca da autonomia; do respeito aos saberes; do comprometimento com uma educação de qualidade e igualitária; da teoria aliada à prática; da aprendizagem que transforma o sujeito e saberes; da relação com o outro; e da aprendizagem pela experiência por meio do diálogo, nos quais o ser e o ambiente são modificados na e pela interação que pode potencializar os processos educativos e de aprendizagem. O percurso metodológico foi de vertente qualitativa, de modo que os dados foram construídos via estudo de caso na Biblioteca Central Hugo Dantas da Silveira, da Universidade Federal do Rio Grande/RS, por meio de análise documental de relatórios de gestão da biblioteca, de entrevistas com bibliotecários atuantes na unidade técnica e grupo focal com usuários. Compuseram a amostra 12 bibliotecários e 7 usuários. Os dados foram tratados por meio da análise textual discursiva, de Moraes e Galiazzi (2003; 2011), e, no cruzamento das análises entre os instrumentos utilizados, identificou-se que os pontos destacados nas narrativas apontam singularidades para configuração da biblioteca universitária. Como considerações finais, essa configuração acarreta novos sistemas e organizações, tanto na ordem e na estrutura de espaços físicos, quanto na organização dos acervos, dos serviços e dos produtos ofertados. A partir das narrativas, foi identificado que os usuários e os bibliotecários atribuem à biblioteca papel fundamental na qualificação das aprendizagens acadêmicas, e a legitimam como espaço que pode se constituir pela democratização do acesso à informação, pela mediação entre a informação e o conhecimento registrado e, principalmente, pela constituição de espaços que contribuam para a aprendizagem. As diretrizes tecidas para reconfiguração da Biblioteca, com base nos dados construídos e analisados nesta investigação, legitimam-na enquanto ambiente de estímulo e constituição para aprendizagem, pois, além de difundir e administrar o conhecimento produzido e armazenado em seus diversos suportes e dispositivos, trabalha para promover ações de busca, interação e disseminação da informação. A pesquisa reitera que a biblioteca no âmbito da aprendizagem é mobilizadora, desempenhando função educacional e mediadora para a democratização do acesso à informação e promotora do conhecimento.
Keywords: Educação; Bibliotecas universitárias; Aprendizagem; Education; Academic libraries; Learning